2017
DOI: 10.18632/oncotarget.17137
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and forensic efficiency of autosomal insertion/deletion polymorphisms in Chinese Bai ethnic group: phylogenetic analysis to other populations

Abstract: Thirty insertion/deletion loci were utilized to study the genetic diversities of 125 bloodstain samples collected from Bai group in Yunnan Dali region, China. The observed heterozygosity and expected heterozygosity of the 30 loci ranged from 0.1520 to 0.5680, and 0.1927 to 0.4997, respectively. No deviations from Hardy-Weinberg equilibrium tests after Bonferroni correction were found at all 30 loci in Bai group. The cumulative probability of exclusion and combined discrimination power were 0.9859 and 0.9999999… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The genetic distances (D A distance) were calculated among Yao, Kelao, and Zhuang samples, and the 20 referenced groups included Beijing Han (Wei et al, 2014), Guangdong Han ( Li et al, 2013), Shanghai Han (Wang et al, 2014), Yi (Liang et al, 2013), Bai (Yang et al, 2017), Xibe (Meng et al, 2015), South Korean (Seong et al, 2014), Tibet Tibetan (Wei et al, 2014), Qinghai Tibetan (Wei et al, 2014), She (Martin et al, 2013), Kazak (Wei et al, 2014), Uigur (Wei et al, 2014), Danes (Friis et al, 2012), Hungarian (Kis et al, 2012), Basque (Martin et al, 2013), Central Spanish (Martin et al, 2013), Uruguaya (Saiz et al, 2014), Jalisco Mexican (Martinez-Cortes et al, 2016), Nigeria (Du et al, 2017), Vietnamese (Du et al, 2017). The result of D A distances was illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic distances (D A distance) were calculated among Yao, Kelao, and Zhuang samples, and the 20 referenced groups included Beijing Han (Wei et al, 2014), Guangdong Han ( Li et al, 2013), Shanghai Han (Wang et al, 2014), Yi (Liang et al, 2013), Bai (Yang et al, 2017), Xibe (Meng et al, 2015), South Korean (Seong et al, 2014), Tibet Tibetan (Wei et al, 2014), Qinghai Tibetan (Wei et al, 2014), She (Martin et al, 2013), Kazak (Wei et al, 2014), Uigur (Wei et al, 2014), Danes (Friis et al, 2012), Hungarian (Kis et al, 2012), Basque (Martin et al, 2013), Central Spanish (Martin et al, 2013), Uruguaya (Saiz et al, 2014), Jalisco Mexican (Martinez-Cortes et al, 2016), Nigeria (Du et al, 2017), Vietnamese (Du et al, 2017). The result of D A distances was illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Investigator DIPplex kit was the first commercial kit developed by Qiagen (Qiagen, Hilden, Germany) for the indel marker. This kit contains 30 autosomal indels and amelogenin, and it has been used to perform systematic investigations on worldwide populations of African (Hefke, Davison & D’Amato, 2015), Asian (Wang et al, 2014; Li et al, 2013; Liang et al, 2013; Meng et al, 2015; Seong et al, 2014; Wei et al, 2014; Yang et al, 2017), European (Friis et al, 2012; Kis et al, 2012; Martin et al, 2013), and American (Saiz et al, 2014) origins. However, very few studies have reported about how indels can be used in comprehending the genetic variation of ethnic minority groups (Zhuang, Yao, and Kelao) in the Guangxi Zhuang Autonomous Region, China.…”
Section: Introductionmentioning
confidence: 99%
“…Population data of 30 DIPs in different continental populations were obtained from previous studies [8, 9, 11, 12, 14, 15, 19–28]. Totally 26 populations were selected for the following study.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, previously reported population data of 30 DIPs in different continental populations [8, 9, 11, 12, 14, 15, 19–28] were gathered and analyzed to solve the three issues. First, we explored whether some DIP loci, like HLD125, HLD99, and HLD118, identified in previous studies [14, 23] were suitable for ancestry analyses of different continental populations.…”
Section: Introductionmentioning
confidence: 99%
“…To comprehensively explore the patterns of genetic affinity between our studied populations and worldwide reference populations, we merged our newly obtained population data with those of 61 worldwide populations. The final database used in the population comparison study included 6483 East Asian individuals from 38 populations [4,5,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], 494 South Asians from three populations [27][28][29], 300 Vietnamese of Southeast Asia [30], 194 West Asians from two populations [31], 621 African individuals from five populations [27,30,32], 984 European individuals from eight populations [4,[31][32][33][34][35] and 1 071 South Americans from eight populations [36,38]. The detailed geographical regions and population sizes of these included populations are submitted in Supplementary Table S1.…”
Section: Reference Databasementioning
confidence: 99%